2018
DOI: 10.1007/s11910-018-0834-6
|View full text |Cite
|
Sign up to set email alerts
|

The Promise of Telemedicine for Movement Disorders: an Interdisciplinary Approach

Abstract: Telemedicine for MDs has been mainly evaluated in Parkinson's disease (PD) and compared to in-office care is cost-effective with similar clinical care, despite the barriers to engagement. However, particular groups including pediatric patients, rare MDs, and the use of telemedicine in underserved areas need further research. Interdisciplinary telemedicine and tele-education for MDs are feasible, provide similar care, and reduce travel costs and travel time compared to in-person visits. These benefits have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 68 publications
3
76
0
6
Order By: Relevance
“…Many CPs in this study implied they had access to movement disorders specialists, but many individuals in the United States and elsewhere may not have access to subspecialty care. Telemedicine and comprehensive care clinics are potential ways to improve access to specialists, but evaluations have shown that their reach and services are limited . Hence, further research is needed to understand how to overcome system‐level barriers of access to high‐quality PCC for PwP.…”
Section: Discussionmentioning
confidence: 99%
“…Many CPs in this study implied they had access to movement disorders specialists, but many individuals in the United States and elsewhere may not have access to subspecialty care. Telemedicine and comprehensive care clinics are potential ways to improve access to specialists, but evaluations have shown that their reach and services are limited . Hence, further research is needed to understand how to overcome system‐level barriers of access to high‐quality PCC for PwP.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, the validity of telemedicine to assess PD patients has been well documented in many studies, which is feasible because most physical examinations can be visualized. 25 Indeed, many core features of the disease, except rigidity and postural reflex impairment, can be videotaped or watched with video consultations. The International Parkinson and Movement Disorder Society has developed a practical step-by-step guide for how to implement telemedicine for a movement disorders clinic on their website, including the example of providers and some regional specifics (https://www.movementdisorders.org/MDS/About/ Committees--Other-Groups/Telemedicine-in-Your-Movement -Disorders-Practice-A-Step-by-Step-Guide.htm).…”
Section: A Special Role Of Telemedicine During the Covid-19 Pandemicmentioning
confidence: 99%
“…Parkinson's disease (PD) is the second most common neurodegenerative disease, and the healthcare burden of this disease is increasing across the world. Recently, telemedicine has been increasingly adopted for managing PD patients, owing to the rising burden, limited availability of specialists, recent evidence of its applicability, and advances in technology (1,2). Furthermore, healthcare services for chronically ill patients, including PD patients, were compromised during the COVID-19 pandemic, owing to the lockdown and the direction of healthcare resources toward its containment.…”
Section: Introductionmentioning
confidence: 99%